Penguatan Kapasitas Pemerintahan Desa Dalam Menjalankan Adminstrasi Pemerintahan Di Desa Batu Winangun - Azwar, Azwar; Meiwinda, Eka Rizki; Lucyana, Lucyana; Hasibuan, Rahmawaty; zulkarnain, Muhammad (Jurnal Dehasen Untuk Negeri, 2025)
The village government, namely the village head and other village officials, have duties and responsibilities as well as obligations to provide services needed by the community, the process of which must go through the village administration. In village administration, governance must run well to prevent unwanted things from happening, such as the loss of valuable assets. This community service aims to educate village officials in working on the village administration and governance system. During the activity, participants actively participated in the activities and studied the governance and administration system. The result of this activity is an increase in the ability and knowledge of village officials in Battu Winangun Village regarding the village administration system and governance.